Feature : Model independence. (14th October 2019) - Massimi, Michela
Abstract: Particle physicists are planning the successor to CERN's Large Hadron Collider – but how will they deal with the deluge of data from a future machine and the proliferation of theoretical models? Michela Massimi explains why a new scientific methodology called "model independence" could hold the answer